2008
DOI: 10.1007/s11262-008-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence analysis of a predominant infectious bronchitis virus (IBV) strain in China

Abstract: Infectious bronchitis (IB) is one of the major diseases in poultry flocks all over the world caused by infectious bronchitis virus (IBV). In the study, the complete genome sequence of strain A2 was sequenced and analyzed, which was a predominant IBV strain in China. The results indicated that there were mutations, insertions, and deletions distributed in the whole genome. The A2 virus had the highest identity to S14 and BJ in terms of full genome, whereas had a further distance to Massachusetts strains. Phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
6
38
0
1
Order By: Relevance
“…These results suggest the need for dynamic and persistent surveillance of IBV in China. Liu et al [36] showed that the A2-like virus, which is a 4/91-serotyperelated virus determined by neutralization test, was the predominant IBV type in chicken flocks. However, more detailed results from the present study, our previous reports [15,23,26] tion against the LX4-type IBV [30] , which suggests a need to develop vaccines from LX-type local strains.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the need for dynamic and persistent surveillance of IBV in China. Liu et al [36] showed that the A2-like virus, which is a 4/91-serotyperelated virus determined by neutralization test, was the predominant IBV type in chicken flocks. However, more detailed results from the present study, our previous reports [15,23,26] tion against the LX4-type IBV [30] , which suggests a need to develop vaccines from LX-type local strains.…”
Section: Discussionmentioning
confidence: 99%
“…Viral genome is around 27.6 kb in length [4,5] and contains a 5 0 cap and a 3 0 -polyadenylated tail. Its genome encodes four structural proteins: phosphorylated nucleocapsid protein (N), membrane glycoprotein (M), spike glycoprotein(S), and small membrane protein (E) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The investigations in IBV isolated from immunized chickens discovered that immunity effect declined partly owing to the genetic variation in the process of IBV evolution [7,22,23,25,30] . We found that more than 40% IBVs belonged to LX4 type, which was circulating prevalently in chicken flocks in China, the result corresponded with the reported literature [20,22,30] .…”
Section: Discussionmentioning
confidence: 99%
“…IBV is an enveloped, non-segmented and singlestranded positive RNA virus with a genome around 27.6-kb in length [5][6][7] . The genome encodes four structural proteins, including spike glycoprotein (S), integral membrane glycoprotein (M), small membrane protein (E) and phosphorylated nucleocapsid (N) protein.…”
Section: Introductionmentioning
confidence: 99%